Implementation of Deep Learning in School Curriculum: Perspectives of Teachers in Nagekeo Regency - Yohanes Freadyanus Kasi; Delviana Vivi Bai; Novia Novia; Saprolla Rollie C. Deporos; Ahmad Dindang Mababaya (Universitas Sebelas Maret, 2025)
Education is the main pillar in forming individuals who are able to face global challenges in the modern era. This study aims to depict teachers' perceptions of deep learning-based instruction, including a deeper understanding of its definition. The subjects in this study consisted of 30 teachers in Nagekeo Regency from elementary to secondary school level. A set of questionnaires consisting of open and closed questions about teachers' perceptions and understanding of deep learning-based instruction and 21st century skills preparation were developed and implemented. Responses from science teachers were analyzed through interpretive methods to gain their understanding and perspectives. The results of the study show that 1) most teachers (83%) know about 21st century skills, 2) deep learning-based instruction is quite well understood (62,4%) by teachers in Nagekeo Regency, 3) the government has paid attention to education but not optimally and 4) 100% of teachers are involved in the subject teacher forum (MGMP). It is important for us to focus on teachers as they play a crucial role in the success of the new reforms. The implication is that there is a great need to raise awareness at the government and teacher levels to embrace deep learning-based instruction.